The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1088/1742-6596/1409/1/012012
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of turbulent syngas/methane/air flames at a sub-atmospheric condition

Abstract: The aim of this work was determined turbulent burning velocities of air-syngas-methane flames at sub-atmospheric conditions using the angle method and Schlieren imaging. We analyzed a high hydrogen content syngas that can be obtained with a Conoco-Phillips coal gasification process. Equivalence ratios evaluated here correspond to lean combustion conditions: 0.8-1.0. Experiments were carried out at room temperature of 297 K and 849 mbar. The chemical-turbulence interaction was evaluated considering geometric pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…To make comparisons of the experimental results obtained in the present work, different theoretical correlations proposed by some authors are plotted. These correlations correspond 8)- (10). Other authors (in ( 11)) using values for the constant C = 1.6 and n = 0.3, same as the doctoral work developed by [16]).…”
Section: Theoretical Correlations To Determine the Turbulent Burning ...supporting
confidence: 53%
See 1 more Smart Citation
“…To make comparisons of the experimental results obtained in the present work, different theoretical correlations proposed by some authors are plotted. These correlations correspond 8)- (10). Other authors (in ( 11)) using values for the constant C = 1.6 and n = 0.3, same as the doctoral work developed by [16]).…”
Section: Theoretical Correlations To Determine the Turbulent Burning ...supporting
confidence: 53%
“…Many correlations between laminar burning velocity and turbulent burning velocity have been studied in general terms by different authors [9][10][11][12]. Studies have also focused on the study of methane and air premix flames, arriving at correlations for the turbulent burning velocity S T = f(S L , u′, P) as a function of laminar burning velocity, turbulence intensity and pressure.…”
Section: Introductionmentioning
confidence: 99%
“…At subatmospheric pressure, the relationship between the normalized burning velocity and normalized turbulent fluctuations was inverted because of the atmospheric condition. Cardona et al 16 studied syngas/methane/air flames at subatmospheric conditions. The equivalence ratios they evaluated correspond to lean combustion conditions: 0.8–1.0.…”
Section: Introductionmentioning
confidence: 99%
“…Flames were generated in a nozzle-type Bunsen burner and then analyzed using Schlieren photography. The experimental setup and methodology to obtain S T which are discussed belowhave been used before by Kobayashi et al, Rangwala et al, , Wang et al, , Cardona et al, and Grover et al for methane and different hydrocarbon mixtures. It has been reported that this methodology is one of the most appropriate one to obtain S T because flames are stationary, and it is possible to perform long-time measurements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation